Fault feature analysis of cracked gear based on LOD and analytical-FE method. (1st January 2018) - Wu, Jiateng; Yang, Yu; Yang, Xingkai; Cheng, Junsheng
Highlights: A new signal decomposition method named LOD is proposed. An new analytical-FE method for the gear tooth crack mesh stiffness is proposed. The assist-SIF method integrates the advantages of AM and FEM. A dynamic model of gear system is estabolished, which combines the LOD method with the assist-SIF method, is used to realize the diagnosis of gear crack. Simulated and experimental signals verify the validity and superiority of LOD method. Abstract: At present, there are two main ideas for gear fault diagnosis. One is the model-based gear dynamic analysis; the other is signal-based gear vibration diagnosis. In this paper, a method for fault feature analysis of gear crack is presented, which combines the advantages of dynamic modeling and signal processing. Firstly, a new time-frequency analysis method called local oscillatory-characteristic decomposition (LOD) is proposed, which has the attractive feature of extracting fault characteristic efficiently and accurately. Secondly, an analytical-finite element (analytical-FE) method which is called assist-stress intensity factor (assist-SIF) gear contact model, is put forward to calculate the time-varying mesh stiffness (TVMS) under different crack states. Based on the dynamic model of the gear system with 6 degrees of freedom, the dynamic simulation response was obtained for different tooth crack depths. For the dynamic model, the corresponding relation between the characteristic parameters and the degree of the tooth crack is established under a specific condition. On the basis of the methods mentioned above, a novel gear tooth root crack diagnosis method which combines the LOD with the analytical-FE is proposed. Furthermore, empirical mode decomposition (EMD) and ensemble empirical mode decomposition (EEMD) are contrasted with the LOD by gear crack fault vibration signals. The analysis results indicate that the proposed method performs effectively and feasibility for the tooth crack stiffness calculation and the gear tooth crack fault diagnosis.